Design of fusion enzymes for biocatalytic applications in aqueous and non-aqueous media - Ma, Yu; Zhang, Ningning; Vernet, Guillem; Kara, Selin (Frontiers in Bioengineering and Biotechnology, 2022)
Biocatalytic cascades play a fundamental role in sustainable chemical synthesis. Fusion enzymes are one of the powerful toolboxes to enable the tailored combination of multiple enzymes for efficient cooperative cascades. Especially, this approach offers a substantial potential for the practical application of cofactor-dependent oxidoreductases by forming cofactor self-sufficient cascades. The adequate cofactor recycling while keeping the oxidized/reduced cofactor in a confined microenvironment benefited from the fusion fashion, makes the use of oxidoreductases in harsh non-aqueous media practical. In this mini-review, we summarized the application of various fusion enzymes in aqueous and non-aqueous media with a focus on the discussion of linker design within oxidoreductases. The design and properties of the reported linkers have been reviewed in detail. Besides, the substrate loadings in these studies were listed to showcase one of the key limitations (low solubility of hydrophobic substrates) of aqueous biocatalysis when it comes to the efficiency and economic feasibility. Therefore, a straightforward strategy of applying non-aqueous media has been briefly discussed while the potential of using the fusion oxidoreductase of interest in organic media was highlighted.